中西醫結合述評: The Integration between Traditional Chinese and Modern Western Medicine: History and Appraisal - LU, Weibo (International Journal of Chinese & Comparative Philosophy of Medicine, 1998)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 中西醫結合包含中醫和西醫之間的團結合作，但更重要的是中醫學和西醫學之間的互相結合。在世界上對傳統醫學曾有過三種方針，即“否定”，“容忍”和“平行”的方針，均不能充分發揮傳統醫學的作用和潛力。中國採取“結合”的方針，較好地解決了這一問題，不僅滿足當前醫療工作的需要，更重要的是在科學研究中，強調創新，兩種醫學的觀點、方法、優勢互補，獲得大量新的研究成果，如針刺原理和針麻研究，青萬素的發現，瘀血證研究等。雖然現代醫學是主流醫學，但尚不足以解決所有問題，如慢性病，老年病等。用結合的思想可以更好地解決各種難題，使醫學科學更快地向前發展，造福於人民。 What attitude should we take toward traditional medicine? There have been three types of policies in this regard all over the world. First, the excluding policy prohibits practicing any traditional medicine. Traditional physicians are not qualified to possess the title of physician, and their practice is illegal. Second, the tolerating policy does not make illegal traditional medical practice, but it does not formally affirm the practice. Third, the paralleling policy allows both traditional and modem medical practices, but their use may not overlap. For example, traditional physicians may not use modem medical facilities. Since the establishment of the People’s Republic of China in 1949, a unique policy of integration has been adopted in China. This policy assumes that both traditional Chinese medicine and modern Western medicine have strengths and weaknesses. It requires that both types of medicine be integrated so as to develop more effective methods in treating diseases and preserving health. There are two senses of the integration of traditional Chinese and modern Western medicine. The first sense refers to the integration of the two types of the physicians, i.e., the cooperation between traditional Chinese practitioners and modern Western medical professionals. The second sense refers to the integration of the two disciplines; i.e., to use both traditional Chinese and modern Western medical theories and practices to create new forms of diagnostic and therapeutic approaches and means. The hope was to have the perspectives, methods, and solutions of both types of medicine complement each other. Under the integrating policy, traditional Chinese medicine has been developed tremendously in mainland China. 30 traditional Chinese medical colleges, 2457 traditional Chinese medical hospitals, and 170 traditional Chinese medical research institutions have been established. A number of well-known medical achievements, such as acupunctural analgesia and anesthesia, the discovery of a new type of anti-malaria drug - Qinghaosu (artemisinin), and the study of blood stasis syndrome, have been made by following the integrating strategy. With the rapid growth and development of the diagnostic and therapeutic technologies in modern Western medicine, some individuals are doubtful of the prospect of traditional Chinese medicine and of the necessity of China’s integrating strategy. However, no matter how advanced modern Western medicine as a form of medicine has become, it will not be able to handle all diseases or medical problems effectively and appropriately. The human body and medical reality are too complicated to be fixed by modern medicine once and for all. For instance, in the present time, chronic and geriatric diseases pose perplexing challenges to modern medicine. Possibilities are always open for traditional Chinese medicine as well as the integrated traditional Chinese and modern medicine to make their valuable contributions. DOWNLOAD HISTORY | This article has been downloaded 69 times in Digital Commons before migrating into this platform.